Leptocoma Cabanis, 1851 (Aves: Nectariniidae) given priority over Chalcostetha Cabanis, 1851 on first reviser principle - Steinheimer, Frank D. (Zootaxa, 2008)
The sunbird genera Chalcostetha and Leptocoma were originally published in the same publication one page apart (Cabanis 1851: 103, 104, respectively). The former genus originally included two species, Nectarinia pectoralis Temminck, 1822: text to plate 138 (= Nectarinia calcostetha Jardine, 1843), and Cinnyris aspasia Lesson & Garnot, 1828: plate 30 (= Cinnyris sericeus Lesson, 1827). G. R. Gray (1855: 19, cit. in Rand 1967) subsequently designated calcostetha the type species of the genus. Shelley (1880: xxv) treated the genus Chalcostetha as monotypic, and was followed in this by Gadow (1884: 12–13) and others. Leptocoma originally included three nominal species: Nectarinia hasseltii Temminck, 1825: text to plate 376 (= Certhia brasiliana J. F. Gmelin, 1788); Certhia zeylonica Linnaeus, 1766; and Certhia sperata Linnaeus, 1766; hasseltii (= brasiliana = sperata) was designated by Cabanis (1851) as type species of the genus (cf. Rand 1967: 223, 236, 237, 240, 242; for availability of generic names see http://www.itis.gov/; http://www.ubio.org/ [both accessed 15 June 2008]; and Neave 1939a, 1939b).